Watercolour landscapes - Taylor, Richard S. (Collins & Brown, 2003)
"The perfect companion for the watercolour landscape painter ; Packed with useful tips, inspiring studies and easy-to-follow projects ; Step-by-step demonstrations showing basic watercolours techniques ; Covering every aspect of landscape painting, from forests and woodlands, hills and mountains to lakes and rivers and skies and clouds, 'Watercolour Landscapes' contains everything you need to paint with confidence" --Cover, p. 4.